Influence of Nanoparticle Reinforcement on the Mechanical Properties of Ultrafine-Grained Aluminium Produced by ARB - Schmidt, Christian; Knieke, Catharina; Maier, Verena; Höppel, Heinz Werner; Peukert, Wolfgang; Göken, Mathias (Materials Science Forum, 2011)
Dispersed nanoparticles are introduced from stabilized suspensions during the accumulative roll bonding process in aluminium AA1050A by air gun spraying up to a final volume fraction of 0.1 % after eight cycles. Additional strengthening caused by particle insertion is observed and strongly depends on the suspension medium and stabilizing agent as both influence interfacial bonding of the particles to the matrix. The particle insertion furthermore results in reduced peel strength of the sheets irrespective of particle material and size caused by a reduction of effective metal to metal bonding area during rolling through the presence of the particle